Legal Protection of Traditional Culinary in the Development of Sustainable Gastronomy Tourism - Bayu Setiawan; Mochammad Rian Ahdian Morena (CV. Era Digital Nusantara, 2026)
This research examines the legal framework governing the protection of traditional culinary heritage in the context of sustainable gastronomy tourism development in Indonesia, with the aim of proposing a comprehensive normative model that integrates intellectual property law, cultural heritage law, and sustainable tourism governance. A normative juridical methodology is employed, encompassing three complementary approaches: statutory analysis, conceptual analysis, and comparative legal analysis across four jurisdictions (Indonesia, EU, Republic of Korea, and Peru). Existing legal instruments including Law No. 28/2014 on Copyright, Law No. 20/2016 on Trademarks and Geographical Indications, Law No. 5/2017 on Cultural Advancement, the UNESCO Convention (2003), and the WIPO Treaty on Traditional Knowledge (2024) constitute foundational but incomplete protective mechanisms. Four principal legal challenges are identified: definitional ambiguity, registration barriers, enforcement deficits, and the tension between protection and accessibility. A five-pillar normative framework is proposed, encompassing legislative consolidation, institutional capacity development, enforcement strengthening, benefit-sharing mechanisms, and international diplomatic engagement, providing a policy roadmap for Indonesia to achieve world-class protection of its traditional culinary heritage.